Mastering MultiMate advantage - Ackerman, Charles (San Francisco : SYBEX, 1987)
This book teaches fundamentals of computing using word-processing program and other elementary tutorials.
On t.p. the registered trademark symbol "TM" is superscript following "Advantage" in the title.
Includes index.
oo 14/01/2019
Loans
Keywords: Word processing